2020
DOI: 10.1016/j.ijrobp.2020.07.081
|View full text |Cite
|
Sign up to set email alerts
|

TGM2 Novel Biomarker Of Radiation Response After Neo-Adjuvant TMZ In Glioblastoma

Abstract: Purpose/Objective(s): Frameless stereotactic radiosurgery (SRS) has become a preferred supplement to frame-based Gamma Knife SRS due to its non-invasive nature and allowance for fractionation. To account for intra-fraction motion, radiation is automatically gated whenever a real-time tracking system detects patient displacement larger than a user-specified threshold. Treatment delivery pauses and a cone-beam CT is acquired to verify patient position if the excess displacement persists. This gating technique, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Daniel and coworkers demonstrated that tTG enhances radio-resistance in glioblastoma both in vitro and in vivo by repressing the expression of the DNA damage repair protein RAD51. 55 They and others have also noted that radiation treatment of glioblastomas frequently resulted in upregulation of tTG. 55,56 Interestingly, Berg demonstrated that irradiation of healthy astrocytes caused tTG to be secreted into the extracellular matrix, which in turn generated a supportive microenvironment for implanted glioma cells, leading to more rapid tumor growth in mouse models.…”
Section: Drug and Radiation Resistancementioning
confidence: 98%
See 1 more Smart Citation
“…Daniel and coworkers demonstrated that tTG enhances radio-resistance in glioblastoma both in vitro and in vivo by repressing the expression of the DNA damage repair protein RAD51. 55 They and others have also noted that radiation treatment of glioblastomas frequently resulted in upregulation of tTG. 55,56 Interestingly, Berg demonstrated that irradiation of healthy astrocytes caused tTG to be secreted into the extracellular matrix, which in turn generated a supportive microenvironment for implanted glioma cells, leading to more rapid tumor growth in mouse models.…”
Section: Drug and Radiation Resistancementioning
confidence: 98%
“…55 They and others have also noted that radiation treatment of glioblastomas frequently resulted in upregulation of tTG. 55,56 Interestingly, Berg demonstrated that irradiation of healthy astrocytes caused tTG to be secreted into the extracellular matrix, which in turn generated a supportive microenvironment for implanted glioma cells, leading to more rapid tumor growth in mouse models. This modified extracellular matrix supported stemness and radio-resistance.…”
Section: Drug and Radiation Resistancementioning
confidence: 98%